Head and neck sarcomas: A single institute series. (February 2017) - Vassiliou, Leandros-Vassilios; Lalabekyan, Bagrat; Jay, Amrita; Liew, Colin; Whelan, Jeremy; Newman, Laurence; Kalavrezos, Nicholas
Highlights: Sarcomas of the head and neck require multimodal treatment. Head and neck osteosarcomas demonstrate different pattern of spread comparing to epithelial cancers. Head and neck sarcomas require wide 'compartmental' excision to achieve control. Head and neck soft tissue sarcomas extending to the skull base are difficult to control. Abstract: Background: Sarcomas are tumours of mesenchymal origin, accounting for 1% of all malignancies. Methods: This is a retrospective analysis of 107 head and neck sarcoma cases, treated over a period of thirteen years. Results: Fifty-four patients had with craniofacial bone sarcomas (BSs) (male: 33; female: 21) with high grade osteosarcoma being the most predominant type. The soft tissue sarcomas (STS) (53 patients; male: 28, female: 25) were histologically diverse with rhabdomyosarcomas and myxofibrosarcomas being the predominant types. The majority of BSs were managed with neoadjuvant chemotherapy followed by surgery, whereas in STSs treatment included predominantly surgery followed by radiotherapy. Overall survival estimates were 79% at 2 years and 64% at 5 years (mean follow-up period was 48 months). Conclusions: The mesenchymal origin of sarcomas, the pattern of disease spread and the different extent of cancellous bone infiltration in contrast to epithelial tumours, dictate distinct principles for surgical clearance.